2020
DOI: 10.1126/scitranslmed.abb2575
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the bond between tetranectin and HMGB1 in sepsis

Abstract: The interaction between tetranectin and high-mobility group box-1 protein may be manipulated via monoclonal antibodies to improve survival in sepsis (Chen et al. same issue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…fully understood, although it has been implicated in multiple bone disorders and wound healing [46]. In this study, TN showed a protective effect against mortality.…”
Section: Plos Onementioning
confidence: 64%
“…fully understood, although it has been implicated in multiple bone disorders and wound healing [46]. In this study, TN showed a protective effect against mortality.…”
Section: Plos Onementioning
confidence: 64%
“…[33,34] Studies showed that CLEC3B not only played an important role in tumorigenesis and metastasis but also in tissue remolding, neuroprotection, and inflammation. [35][36][37] CRTAC1, which belongs to the beta-propeller protein, is produced by chondrocytes and alveolar AT2 cells in the human body. [38] Yang et al claimed that CRTAC1 inhibited bladder cancer proliferation migration and invasion by inactivating the TGF-β pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we have developed a panel of TN-specific mAbs that effectively prevented both harmful HMGB1/TN interaction and resultant macrophage pyroptosis and lethal sepsis [ 172 ]. It suggested that TN domain-specific mAbs may confer protection against lethal sepsis partly by preventing harmful TN/HMGB1 interaction that may adversely trigger macrophage pyroptosis and immunosuppression ( Figure 5 ) [ 173 , 174 ]. This antibody strategy has also suggested a possibility to develop therapeutic antibodies against harmless proteins colluding with sepsis mediators [ 173 , 174 , 175 ].…”
Section: Pharmacological Modulation Of Lps-induced Hmgb1 Release or Actionmentioning
confidence: 99%
“…It suggested that TN domain-specific mAbs may confer protection against lethal sepsis partly by preventing harmful TN/HMGB1 interaction that may adversely trigger macrophage pyroptosis and immunosuppression ( Figure 5 ) [ 173 , 174 ]. This antibody strategy has also suggested a possibility to develop therapeutic antibodies against harmless proteins colluding with sepsis mediators [ 173 , 174 , 175 ].…”
Section: Pharmacological Modulation Of Lps-induced Hmgb1 Release or Actionmentioning
confidence: 99%
See 1 more Smart Citation